2019
DOI: 10.21203/rs.2.11434/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A qualitative study of old patients’ experiences of the quality of the health services in hospital and 30 days after hospitalization

Abstract: Background The number of people aged 80 years and above is projected to triple over the next 30 years. People in this age group normally have at least two chronic conditions (multimorbidity). The impact of multimorbidity is often significantly greater than expected from the sum of the effects of each condition. The World Health Organization has indicated that health care systems must prepare for a change in the focus of clinical care for older people. The WHO defines health care quality as care that is effect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Quality healthcare services are examined in the context of the quality of emergency care (Okoroh et al, 2020) as well as the quality of maternal and childcare delivery (Atinga et al, 2018). Others focus on the quality of clinical care for the elderly (Lilleheie et al, 2020). The World Health Organisation (2018) looks at quality healthcare from six dimensions: when the service is effective, efficient, patient-centred, integrated, equitable and safe for the people.…”
Section: Quality Healthcare Service Dimensions and Perspectives On Ghana's Health Insurance Schemementioning
confidence: 99%
“…Quality healthcare services are examined in the context of the quality of emergency care (Okoroh et al, 2020) as well as the quality of maternal and childcare delivery (Atinga et al, 2018). Others focus on the quality of clinical care for the elderly (Lilleheie et al, 2020). The World Health Organisation (2018) looks at quality healthcare from six dimensions: when the service is effective, efficient, patient-centred, integrated, equitable and safe for the people.…”
Section: Quality Healthcare Service Dimensions and Perspectives On Ghana's Health Insurance Schemementioning
confidence: 99%
“…This is also aligned with our finding of adult-child caregivers reporting to be more actively involved in healthcare encounters, giving and receiving information. Although not reported in the caregiver population, a qualitative study in Norway involving older patients reported older patients in inpatient setting experiencing poor communication, lack of clear information and coordination [ 47 ]. Another study reported that patients’ perception of communication with healthcare providers varied with age of the patients [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Being seen as an object and the feeling of being excluded in the transition process were experienced in different ways. In some instances, older patients addressed it as a feeling of being invisible rather than being informed about the discharge and transition plan, as well as potentially feeling disempowered from moving on with their lives at the current stage of their illness [22,23]. Accordingly, this approach created suffering for both patients and relatives and especially forced older patients to take on a passive role [23].…”
Section: Being Excluded Vs Being Included In the Transition Processmentioning
confidence: 99%
“…In some instances, older patients addressed it as a feeling of being invisible rather than being informed about the discharge and transition plan, as well as potentially feeling disempowered from moving on with their lives at the current stage of their illness [22,23]. Accordingly, this approach created suffering for both patients and relatives and especially forced older patients to take on a passive role [23]. Although many patients chose to accept their passive role by putting their trust in the health care professionals [24,30], there was also exhaustion, insecurity, and concern due to the experienced one-way communication [23].…”
Section: Being Excluded Vs Being Included In the Transition Processmentioning
confidence: 99%